Comparing pre-service teacher attitudes toward the use of students’ home language(s) in linguistically diverse English as an additional language classrooms in Norway and Cyprus - Neokleous, Georgios; Karpava, Sviatlana (Frontiers in Education, 2023)
Globalization, increased transnational mobility, and growing refugee populations have shifted the focus from traditionally monolingual to incrementally multilingual and multicultural classrooms and have put a significant mark on language teaching. Attention to multilingualism and multiculturalism in educational settings is important to raising awareness and recognition of linguistic and cultural diversity at the individual and societal levels. This comparative study investigated the beliefs of 59 preservice teachers in Norway and Cyprus regarding the use of students' home language(s) (HLs) in increasingly linguistically diverse English as an Additional Language (EAL) settings. The teachers were observed during their teaching practicum and were interviewed with respect to their views, beliefs, and self-reflections on the impact and role of HL for EAL teaching and learning purposes. The analysis of the data revealed that more than half of the participants in both countries were in favor of employing multilingual pedagogies. However, most of them acknowledged certain challenges in their practical implementation and the need for further training. The study concludes with the authors stressing the catalyst role teacher educators could play in making EAL classrooms more inclusive for multilingual learners.